Kedudukan Anak Bungsu Laki-Laki Terhadap Rumah Peninggalan Orangtua Perspektif Adat Jawa dan Adat Batak Angkola: Studi Kasus di Kecamatan SOSA - Adi Jungkar Harahap; Arifin Marpaung (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study discusses the psition of the youngest son regarding inherited houses based on the perspective of jawa customary law and batak angkola customary law. In the context of Indonesia’s culturally and legally plural society the aim of this article is to examine and compare the Jawa and Batak angkola customs concerning the position of the youngest son in relation to inherited family houses. It also seeks to reveal the faktors influencing the differences in the role of the youngest son in Jawa and Batak angkola traditions. The focus of this research is a case study in Sosa district. This study uses a comprative method with a qualitative approach, conducted through field studies in Sosa districtas the case study location. Data were collected through field observations, intervews with traditional leaders, religious figures, and family members who have directly experienced such issues. This research is expectedto contribute to the advancement of legal development in Indonesia, serve as a reference in the formulation of culturally oriented justice policies, and provide benefits to both the author and readers in general, as well as to Indonesian society at large.